2022
DOI: 10.1111/sms.14197
|View full text |Cite
|
Sign up to set email alerts
|

Combined association of walking pace and grip strength with incident type 2 diabetes

Abstract: The current study aims to investigate the combined association of walking pace and grip strength with incident type 2 diabetes (T2D). A total of 205 738 participants (mean age 56.6 ± 8.1 years, 115 139 [56.0%] women) without diagnosed or unknown diabetes at baseline from the UK Biobank study were included in this prospective study. Walking pace was self-reported as slow, average, or brisk. Grip strength was measured using a dynamometer and classified as weak, average, and strong. The combined association of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Grip strength is more likely a measure of contraction strength whereas walking pace integrates strength with other processes, such as balance and coordination. As such, the combination of both may result in a stronger association with health outcomes than individually [ 20 ]. Previous studies have evaluated the combination of walking pace and grip strength on cardiovascular disease (CVD) [ 21 , 22 ] and type 2 diabetes [ 20 ] and suggested that the combination of walking pace and grip strength was more strongly associated with health outcomes than in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grip strength is more likely a measure of contraction strength whereas walking pace integrates strength with other processes, such as balance and coordination. As such, the combination of both may result in a stronger association with health outcomes than individually [ 20 ]. Previous studies have evaluated the combination of walking pace and grip strength on cardiovascular disease (CVD) [ 21 , 22 ] and type 2 diabetes [ 20 ] and suggested that the combination of walking pace and grip strength was more strongly associated with health outcomes than in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the combination of both may result in a stronger association with health outcomes than individually [ 20 ]. Previous studies have evaluated the combination of walking pace and grip strength on cardiovascular disease (CVD) [ 21 , 22 ] and type 2 diabetes [ 20 ] and suggested that the combination of walking pace and grip strength was more strongly associated with health outcomes than in isolation. In addition, previous studies on the associations of walking pace and handgrip strength on cognitive decline [ 23 , 24 ] have reported that when grip strength and walking pace were included in a regression model simultaneously, only walking pace was associated with cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the concern that inflammation may be a factor to consider because it can affect how vitamin D works in the body [ 30 ]. Although most previous studies have focused on cardiovascular diseases only, the combination of walking pace and grip strength suggests a stronger association with health outcomes than in isolation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a combination of the two may be more relevant to health outcomes than use alone. 14,15 However, to date, the combined effect of grip strength and walking pace on the risk of PD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from a physiological perspective, grip strength and walking pace may reflect different underlying physiological processes: Grip strength is more likely a measure of contraction strength, while walking pace integrates strength with other processes (e.g., balance and coordination). Therefore, a combination of the two may be more relevant to health outcomes than use alone 14,15 . However, to date, the combined effect of grip strength and walking pace on the risk of PD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%